2016
DOI: 10.15740/has/ijcbm/9.1/113-118
|View full text |Cite
|
Sign up to set email alerts
|

Role and importance of public private partnerships in agricultural value chain and infrastructure

Abstract: Changing consumer demand preferences, increasing concern for food safety, traceability and assured year-round availability of quality agri produce at reasonable prices at the top of the supply chain has changed agricultural landscape. Agri infrastructure at different levels of agri value chain is key to a vibrant and competitive agriculture and agro industrial sector. Public Private Partnerships could be a useful tool to accelerate development in various areas of agribusiness and infrastructure. The paper disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Most important is to generate awareness among farmers and stakeholders relevant to their services, rights, making them aware of the positive aspects of PPP and demonstrating the complete transparent paradigm protocol to them. Marbaniang et al [36] has demonstrated an articulate picture of the various PPP models with appropriate role of public and private sectors in agriculture R&D using the source from Shukla et al [44]. We have demonstrated it pictorially in Fig.…”
Section: Page 173mentioning
confidence: 88%
See 1 more Smart Citation
“…Most important is to generate awareness among farmers and stakeholders relevant to their services, rights, making them aware of the positive aspects of PPP and demonstrating the complete transparent paradigm protocol to them. Marbaniang et al [36] has demonstrated an articulate picture of the various PPP models with appropriate role of public and private sectors in agriculture R&D using the source from Shukla et al [44]. We have demonstrated it pictorially in Fig.…”
Section: Page 173mentioning
confidence: 88%
“…From Fig.8, we find that each model signifies the aim of the project with specific role of each member of the consortium from design, project building, management, finance, land leasing authorities, sharing risks and profits to technology transfer. Before furnishing any PPP project, appropriate paradigm protocol with transparent line chain describing rights and duties of each participant should be well defined and planned under secured legal documents[44,45]. It will not only provide security to the stakeholders but will also make them enthusiastic to give their inputs.…”
mentioning
confidence: 99%
“…Private sector participation entails investments aimed at establishing cutting-edge infrastructure, while the public sector offers policy support and fosters an investmentfriendly environment. Public-private partnerships could be a useful tool to accelerate development in various areas of agribusiness and infrastructure (R Shukla 2016) [15] .…”
Section: Infrastructure Development: Ppps Have the Potentialmentioning
confidence: 99%
“…These difficulties have an impact on farmers' livelihoods and the sector's overall expansion. Public Private Partnerships (PPPs) in the agricultural supply chain have the potential to enhance food safety, traceability, and year-round availability of quality produce at reasonable prices (Shukla, 2016) [15] . These partnerships can also help smallholders meet stringent food safety requirements and remain competitive in developed country markets (Narrod, 2009) [12] .…”
Section: Introductionmentioning
confidence: 99%
“…The WeF and McKinsey (2013) observed that agri-PPPs could modernise the agriculture sector and deliver multiple benefits that can contribute to the pursuit of sustainable agricultural development, including among smallholding farmers. Ponnusamy (2013) indicated that PPPs are among the best proven strategies for achieving specific goals within a time frame, particularly for modernising public services, developing agricultural infrastructure, and offering extension services. reasons for the evolution of PPPs in various fields include the lack of facilities, human resources, and time.…”
Section: Introductionmentioning
confidence: 99%